Maluliyet Kalıcı Bedensel Hasarların Değerlendirilmesi - Çetin, Ebubekir; Dokgöz, Halis; Can, İsmail Özgür; Savaş, Çağdaş; Ünaldı, Şeyma Tuğçe; Kalemci, Orhan; Poyraz, Turan; Ergönen, Akça Toprak; Aydoğdu, Halil İlhan; Akpınar, Ramazan; Kurt, Ceren Görkem; Kaya, Kenan; et al. (2024)
-